Blue fluorescent cGMP sensor for multiparameter fluorescence imaging. - Yusuke Niino (Public Library of Science (PLoS), 2010)
Cyclic GMP (cGMP) regulates many physiological processes by cooperating with the other signaling molecules such as cyclic AMP (cAMP) and Ca(2+). Genetically encoded sensors for cGMP have been developed based on fluorescence resonance energy transfer (FRET) between fluorescent proteins. However, to analyze the dynamic relationship among these second messengers, combined use of existing sensors in a single cell is inadequate because of the significant spectral overlaps. A single wavelength indicator is an effective alternative to avoid this problem, but color variants of a single fluorescent protein-based biosensor are limited. In this study, to construct a new color fluorescent sensor, we converted the FRET-based sensor into a single wavelength indicator using a dark FRET acceptor. We developed a blue fluorescent cGMP biosensor, which is spectrally compatible with a FRET-based cAMP sensor using cyan and yellow fluorescent proteins (CFP/YFP). We cotransfected them and loaded a red fluorescent probe for Ca(2+) into cells, and accomplished triple-parameter fluorescence imaging of these cyclic nucleotides and Ca(2+), confirming the applicability of this combination to individually monitor their dynamics in a single cell. This blue fluorescent sensor and the approach using this FRET pair would be useful for multiparameter fluorescence imaging to understand complex signal transduction networks.